The Trap of Incrementalism in Recognising Children's Right to Vote. Issue 2 (3rd April 2021) - Munn, Nick
ABSTRACT: Thirty years on from the Convention on the Rights of the Child, the international norm for the age of political majority remains set at 18 years of age. With few exceptions, those under 18 are denied the right to vote in elections, local or national. Practical efforts to open this new frontier for human rights have primarily been focused on the incremental inclusion of older children into the franchise, via attempts to lower the voting age to 16. By contrast, theoretical arguments, particularly from philosophers, have defended a much more expansive position on the inclusion of children—lowering the age to 14, 12, or even eliminating age limits entirely. I argue that proponents of children's enfranchisement should pursue enfranchisement of all children who have a strong claim to political inclusion, rather than merely those closest to 18 years of age. Enfranchisement is itself empowering, as is the participation which follows. A commitment to theoretically more defensible but politically less likely positions could work to the advantage of children, by making moves such as the lowering of the voting age a reasonable compromise position, rather than an extreme to be opposed.